Integrated analysis of carotenoid metabolites and transcriptome identifies key genes controlling carotenoid compositions and content in sweetpotato tuberous roots (Ipomoea batatas L.) - Jia, Ruixue; Zhang, Rong; Gangurde, Sunil S.; Tang, Chaochen; Jiang, Bingzhi; Li, Guilan; Wang, Zhangying (Frontiers in Plant Science, 2022)
Sweet potato (Ipomoea batatas L.) with different depths of yellow color contains different compositions of carotenoids, which are beneficial for human health. In this study, we performed an integrated analysis of metabolomic and transcriptomic to identify key genes playing a major role in carotenoid coloration in sweet potato tuberous roots. Herein, 14 carotenoids were identified in five sweet potatoes. Orange-red and orange cultivars were dominated by β-carotene (385.33 μg/g and 85.07 μg/g), yellow cultivar had a high β-cryptoxanthin (11.23 μg/g), light-yellow cultivar was rich in zeaxanthin (5.12 μg/g), whereas lutein (3.34 μg/g) was the main carotenoid in white cultivar. Furthermore, 27 differentially expressed genes involved in carotenoid metabolism were identified based on comparative transcriptome. Weighted gene co-expression network analysis identified 15 transcription factors highly associated with carotenoid content in sweet potatoes. These results provide valuable information for revealing the regulatory mechanism of carotenoid metabolism in different-colored sweet potato tuberous roots.